ON THE VALIDITY OF TREATMENT OPTIONS IN EPISTAXIS: AN ANALYSIS OF 61 INTERVENTIONS - Tanvir Hussain; Enas Alaqeab; Sarwar Attique; Alaa Almanassra (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Epistaxis is a common otorhinolaryngological emergency often requiring hospital intervention. Rapid rhino (RR) tamponade is an emerging option, but efficacy data is limited. The study aimed at assessing success rates, failure patterns, and the need for additional procedures using an RR protocol for admitted patients with epistaxis. Methods: A retrospective cohort study conducted at Limerick University Hospital ENT department analyzed 61 consecutive admitted adult epistaxis cases between 1/03/2023 to 31/10/2023. All underwent RR insertion (7.5 or 9.5cm devices depending on laterality) after decongestants and silver nitrate cautery failed. Results: Total n=61; median age 52 years, 75% male. Equal unilateral versus bilateral incidence. Anterior epistaxis n=51 (84%) was controlled successfully with RR alone. Posterior bleeds (n=10,16%) failed RR requiring additional measures. Overall primary success rate was 98% with RR insertion alone. Supplementary interventions entailed posterior balloon inflation packing in 10 (16%) and sphenopalatine artery ligation in 2 (3%). Conclusions: RR insertion was a highly efficacious first-line epistaxis treatment in this representative cohort, with 98% success rates overall for anterior bleeds. Failure patterns revealed increased refractoriness amongst posterior haemorrhage. By validating efficacy while quantifying interventions needed upon RR failure, the study endorses an RR-based institutional protocol while precisely guiding future resource allocation.